Mapeamento do processo de Helpdesk - Dutra, Mariana Nassar (Universidade do Vale do Rio dos Sinos, 2012)
The following research has the objective of mapping the Help Desk process of the company named CYZ (fictional name to protect the company’s privacy). This process was chosen because of the importance support control procedures have to the company. A bibliographic revision was achived regarding what is process, Help Desk process, Business Process Management (BPM) and it’s benefits, the concept of indicators, an explanation of the BPMN notation and the cycle of BPM. Through interviews, the current process situation was identified, it’s existing problems, and the suggestion of enhancements through a BPM tool (the Bizagi) for mapping and documentation. The results obtained in this research show that the usage of this methods will improve the process’ control and padron.
Keywords: Indicadores; Business process management; BPM; Indicators; Help desk; Bizagi; BPMN